2001
DOI: 10.1023/a:1009560330359
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The four ERBB receptors and their multiple polypeptide ligands are differentially expressed during development of the mouse mammary gland. Profiles suggest that ERBB1/EGF receptor (EGFR)4 and ERBB2/Neu are required during ductal morphogenesis, whereas the Neuregulin (NRG) receptors, ERBB3 and ERBB4, are preferentially expressed through alveolar morphogenesis and lactation. Consistent with these profiles, recent gene knockouts established that EGFR and its ligand, Amphiregulin (AR), are essential for ductal mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…For example, both HB-EGF and Betacellulin bind ErbB-1, but mice defective for each factor display distinct phenotypes (41). Another example relates to mammary development, which seems to involve nonoverlapping activities of several ligands of ErbB-1 (42). In this respect, EPG displays unique features, including specificity to ErbB-1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both HB-EGF and Betacellulin bind ErbB-1, but mice defective for each factor display distinct phenotypes (41). Another example relates to mammary development, which seems to involve nonoverlapping activities of several ligands of ErbB-1 (42). In this respect, EPG displays unique features, including specificity to ErbB-1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that estrogens induce ductal elongation during puberty acting through the ER␣ in the mammary epithelium by a paracrine mechanism. EGFR signaling has been implicated downstream of estrogen signaling in the mammary gland (6), and several EGF family members, such as EGF, TGF␣, and amphiregulin, are induced by estrogens in different breast cancer cell lines (20)(21)(22). To test whether EGF family members are regulated by estrogen in vivo in the puberal mammary gland at a time of exponential cell expansion, we mimicked the beginning of puberty in a controlled fashion.…”
Section: Transcriptional Regulation Of Egf Family Members By Estrogenmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) signaling pathway has long been implicated in mammary gland development and human breast cancer (6). EGFR, a member of the ErbB receptor tyrosine kinase family (7), is activated by members of the EGF-like family of ligands, including EGF, transforming growth factor ␣ (TGF-␣), amphiregulin, heparin binding-EGF (HB-EGF), betacellulin (BTC), and epiregulin (EPR).…”
mentioning
confidence: 99%
“…Normal epithelial cells as well as cancer cells usually express more than one ErbB receptor (15,56). During proliferative phases in the cyclic development of some organs, e.g.…”
Section: Fig 6 Egf-induced Activation Of P38 Mapk Pathway In Skbr3/mentioning
confidence: 99%